Anticancer and Antimicrobial Activity Evaluation of Cowpea-Porous-Starch-Formulated Silver Nanoparticles. (10th May 2021) - Ramdath, Shiara; Mellem, John; Mbatha, Londiwe Simphiwe
Abstract : Health issues involving inadequate treatment of diseases such as cancer and microbial infections continue to be the subject of much ongoing recent research. Biosynthesized silver nanoparticles (AgNPs) were characterized using Transmission Electron Microscopy (TEM), Zeta Sizer, Ultraviolet (UV), and Fourier Transform Infrared (FTIR) spectroscopy. Their antimicrobial activity was evaluated on selected Gram-positive and Gram-negative bacterial strains, using the disc diffusion and broth dilution assays. Cell viability profiles were evaluated using MTT (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide) and apoptosis studies on selected human noncancer and cancer cells. The biosynthesized AgNPs were evaluated to be spherical clusters, with sizes between 40 and 70 nm. The absorption peak at 423 nm and the presence of polyphenols confirmed the synthesis and stabilization of these tested AgNPs. The AgNPs showed a good stability of −23.9 ± 1.02 mV. Good antimicrobial activity (6.0–18.0 mm) was seen on all tested bacteria at a minimum inhibitory concentration (MIC) ranging from 5 to 16 μ g/ml, with the highest activity seen against Gram-negative Escherichia coli (18 ± 0.5 mm), and the lowest activity was seen against Gram-positive Listeria monocytogenes (6.0 ± 0.4 mm) after treatment with the AgNPs. These NPs showed a concentration-dependent and cell-specific cytotoxicity with low IC50 values (41.7, 56.3, and 63.8 μ g/ml). The NPs were well tolerated by tested cells as indicated by a more than 50% cell viability at the high dose tested and low apoptotic indices (<0.2). These findings indicated that these biosynthesized AgNPs showed great potential as effective antibacterial agents and anticancer drug delivery modalities.